Bureaucratic accountability in third‐party governance: Experimental evidence of blame attribution during times of budgetary crisis. (18th July 2017) - Piatak, Jaclyn; Mohr, Zachary; Leland, Suzanne
Abstract : With the rise of third‐party government, the lines between the sectors have blurred as has accountability. Public service delivery failures can erode government legitimacy and trust, but who do citizens blame when something goes wrong? To answer this question, we employ an experiment to see whether citizens hold local governments and private contractors equally accountable for service delivery failure. We also examine how they expect the employees to be held accountable. Results demonstrate that blame is attributed to those providing the service directly. However, the introduction of a budget shortfall lessens the blame assigned to the contractor, and implicates the city even when the service is provided indirectly through a contract. Finally, citizens are less in favour of terminating the employment of both public and contract employees under budget shortfalls. Findings suggest that if citizens are given information about the context and who is in control of the service, they attribute blame accordingly.